2014
DOI: 10.1371/journal.pone.0112781
|View full text |Cite
|
Sign up to set email alerts
|

Keratocytes Derived from Spheroid Culture of Corneal Stromal Cells Resemble Tissue Resident Keratocytes

Abstract: PurposeCorneal stromal cells transform to precursor cells in spheroid culture. We determined whether keratocytes derived from spheroid culture of murine corneal stromal cells resemble tissue resident keratocytes.MethodsSpheroid culture was performed by seeding dissociated stromal cells onto ultra-low attachment plates containing serum-free mesenchymal stem cell culture medium. Spheroids were characterized with phenotype specific markers and stemness transcription factor genes. Spheroids and adherent cells in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…This suggests that there was only partial differentiation of the cells to the keratocyte phenotype, in all media. In many instances, in vitro keratocyte differentiation has only been demonstrated by increased expression of keratocyte markers, but has not been confirmed by a simultaneous decrease in fibroblast markers such as CD90 and vimentin (Berryhill et al ., ; Byun et al ., ; Foster et al ., ; Gouveia and Connon ; Park et al ., ). The only differences seen between the differentiation media in this study were a downregulation of NT5E in media containing RA and differences in α‐SMA expression; α‐SMA fibre staining was not seen in cultures supplemented with FGF‐2.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there was only partial differentiation of the cells to the keratocyte phenotype, in all media. In many instances, in vitro keratocyte differentiation has only been demonstrated by increased expression of keratocyte markers, but has not been confirmed by a simultaneous decrease in fibroblast markers such as CD90 and vimentin (Berryhill et al ., ; Byun et al ., ; Foster et al ., ; Gouveia and Connon ; Park et al ., ). The only differences seen between the differentiation media in this study were a downregulation of NT5E in media containing RA and differences in α‐SMA expression; α‐SMA fibre staining was not seen in cultures supplemented with FGF‐2.…”
Section: Discussionmentioning
confidence: 99%
“…ASCs, UCSCs, and BMMSCs have been shown to improve corneal opacity in vivo with differentiation of the MSCs into keratocytes after they have been applied to the injured or scarred cornea 2022. Studies have shown that human MSCs derived from different tissues can differentiate toward the keratocyte lineage in vitro, and these MSC types include ASCs,52,5860 BMMSCs,21 periodontal ligament stem cells,27,29 dental pulp stem cells,26 UCSCs,28 turbinate-derived MSCs,23 and CSSCs 8,25,61. However, there is no direct comparative study of keratocyte differentiation of MSCs derived from different tissue types.…”
Section: Discussionmentioning
confidence: 99%
“…Human and mice Co-MSCs were isolated and expanded as described before. 1 , 2 , 14 , 15 Briefly, the corneoscleral button from healthy cadaver eyes (provided by Eversight Eye Bank, Ann Arbor, MI, USA) or freshly enucleated mouse eyes were washed five times with PBS containing 2X Antibiotic-Antimycotic and 2X penicillin- streptomycin (both from Thermo Fisher Scientific, Waltham, MA, USA). After removing the central button with a trephine, the limbus was cut into three segments that were placed in 2.4 IU of protease (Dispase II; Thermo Fisher Scientific) for 1 hour at 37°C.…”
Section: Methodsmentioning
confidence: 99%